Atomic layer deposition of yttria-stabilized zirconia thin films for enhanced reactivity and stability of solid oxide fuel cells. (1st December 2016) - Park, Joonho; Lee, Yeageun; Chang, Ikwhang; Cho, Gu Young; Ji, Sanghoon; Lee, Wonyoung; Cha, Suk Won
Abstract: We report the advantages of atomic layer deposition (ALD) for the fabrication of yttria-stabilized zirconia (YSZ) electrolyte. The reactivity and stability of anodic aluminum oxide (AAO)-based thin-film solid oxide fuel cells (SOFCs) are improved by applying ALD YSZ electrolyte. The fuel cell fabricated by ALD shows a peak power density of 154.6 mW cm −2 at 450 °C, whereas the fuel cell fabricated by sputtering demonstrates a peak power density of 66.2 mW cm −2 . The amorphous and nanogranular microstructure of the ALD YSZ film is ascribed for a significant improvement in the cathodic reactivity of the AAO-based thin-film fuel cells. Moreover, the smooth and uniform surface of the ALD YSZ electrolytes mitigates the agglomeration of the Pt cathode layer, and thus the thermal stability of the thin-film fuel cell is remarkably improved at 450 °C. Highlights: Atomic layer deposition (ALD) and sputter were used for thin film YSZ fabrication. Advantages of ALD YSZ layer for thin-film SOFC cathodes were investigated. ALD YSZ improves both reactivity and thermal stability of thin-film SOFC cathodes. Causes for reactivity and stability improvement were studied. Combined thin-film YSZ deposition method was developed for effective fabrication.